Ancient Mesopotamia speaks (New Haven)
xi, 306 sayfa
Keywords: “A stunning guide to the treasures housed within the Yale Babylonian Collection, presenting new perspectives on the society and culture of the ancient Near East, The Yale Babylonian Collection houses virtually every genre, type, and period of ancient Mesopotamian writing, ranging from about 3000 B.C.E. to the early Christian Era. Among its treasures are tablets of the Epic of Gilgamesh and other narratives, the world's oldest recipes, a large corpus of magic spells and mathematical texts, stunning miniature art carved on seals, and poetry by the first named author in world history, the princess Enheduanna.This unique volume, the companion book to an exhibition at Yale's Peabody Museum of Natural History, celebrates the Yale Babylonian Collection and its formal affiliation with the museum. Included are essays by world-renowned experts on the exhibition themes, photographs and illustrations, and a catalog of artifacts in the collection that present the ancient Near East in the light of present-day discussion of lived experiences, focusing on family life and love, education and scholarship, identity, crime and transgression, demons, and sickness“--